The Architecture of Inactivated SARS-CoV-2 with Postfusion Spikes Revealed by Cryo-EM and Cryo-ET - Liu, Chuang; Mendonça, Luiza; Yang, Yang; Gao, Yuanzhu; Shen, Chenguang; Liu, Jiwei; Ni, Tao; Ju, Bin; Liu, Congcong; Tang, Xian; Wei, Jinli; Ma, Xiaomin; et al. (Structure (London), 2020)
The ongoing global pandemic of coronavirus disease 2019 (COVID-19) resulted from the outbreak of SARS-CoV-2 in December 2019. Currently, multiple efforts are being made to rapidly develop vaccines and treatments to fight COVID-19. Current vaccine candidates use inactivated SARS-CoV-2 viruses; therefore, it is important to understand the architecture of inactivated SARS-CoV-2. We have genetically and structurally characterized β-propiolactone-inactivated viruses from a propagated and purified clinical strain of SARS-CoV-2. We observed that the virus particles are roughly spherical or moderately pleiomorphic. Although a small fraction of prefusion spikes are found, most spikes appear nail shaped, thus resembling a postfusion state, where the S1 protein of the spike has disassociated from S2. Cryoelectron tomography and subtomogram averaging of these spikes yielded a density map that closely matches the overall structure of the SARS-CoV postfusion spike and its corresponding glycosylation site. Our findings have major implications for SARS-CoV-2 vaccine design, especially those using inactivated viruses. [Display omitted] •β-propiolactone-inactivated SARS-CoV-2 viruses display postfusion spikes•Cryo-ET structure of SARS-CoV-2 postfusion spikes was determined at 11 Å resolution•This study calls for crucial structural characterization of vaccine candidates Several vaccine candidates using inactivated SARS-CoV-2 viruses are under development. Liu et al. used state-of-the-art cryoelectron microscopy technologies to characterize the architecture of inactivated SARS-CoV-2 viruses. They found that the viral spikes are mostly in a postfusion state, which is not desirable for vaccine development.